2004
DOI: 10.1016/s0896-6273(04)00074-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y-Mediated Inhibition of Proopiomelanocortin Neurons in the Arcuate Nucleus Shows Enhanced Desensitization in ob/ob Mice

Abstract: NPY and alphaMSH are expressed in distinct neurons in the arcuate nucleus of the hypothalamus, where alphaMSH decreases and NPY increases food intake and body weight. Here we use patch-clamp electrophysiology from GFP-labeled POMC and NPY neurons to demonstrate that NPY strongly hyperpolarized POMC neurons through the Y1R-mediated activation of GIRK channels, while the alphaMSH analog, MTII, had no effect on activity of NPY neurons. While initially NPY had similar effects on POMC neurons derived from ob/ob mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
135
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(152 citation statements)
references
References 36 publications
(2 reference statements)
15
135
2
Order By: Relevance
“…Previous studies have suggested that postsynaptic NPY actions may be attributable to Y 1 receptor activation (Rhim et al, 1997;Sun et al, 2001b;Sun et al, 2003;Fu et al, 2004;Roseberry et al, 2004). Our results were consistent with this.…”
Section: Ionic Mechanisms Of Npy Actions On Arc Gaba Cellssupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have suggested that postsynaptic NPY actions may be attributable to Y 1 receptor activation (Rhim et al, 1997;Sun et al, 2001b;Sun et al, 2003;Fu et al, 2004;Roseberry et al, 2004). Our results were consistent with this.…”
Section: Ionic Mechanisms Of Npy Actions On Arc Gaba Cellssupporting
confidence: 93%
“…5A, trace 1 (Doods et al, 1996;Sun et al, 2003) (Doods et al, 1999), did not block the hyperpolarization induced by 100 nM [Pro 34 ]NPY 1-36 (n ϭ 6) (Fig. 5C In other hypothalamic neurons, postsynaptic NPY actions have been shown to depend mainly on the activation of Y 1 receptor (Rhim et al, 1997;Fu et al, 2004;Roseberry et al, 2004). In hypothalamic slices incubated with 1 M BIBP3226, NPY still hyperpolarized ARC GABA neurons by 5.2 Ϯ 1.4 mV (n ϭ 5; p Ͻ 0.05) (data not shown), suggesting that another NPY receptor, in addition to Y 1 , is involved in the postsynaptic actions of this peptide.…”
Section: Direct Postsynaptic Npy Actions Via Y 1 and Y 2 Receptor Submentioning
confidence: 97%
See 1 more Smart Citation
“…These numbers were nonetheless within the range of that recently shown to be sufficient to stimulate food intake (∼300 neurons and above) (39). By contrast, labeling of POMC neurons was more surprising given that ghrelin is generally acknowledged to indirectly target this population via GHS-R-1a-expressing presynaptic NPY neurons (25,40). Together with ex vivo studies demonstrating direct effects of ghrelin on POMC neuron electrical activity (25), our results clearly suggest that POMC neurons may be a direct target for ghrelin in vivo.…”
Section: Discussionmentioning
confidence: 64%
“…25 It is expressed mainly in orexigenic NPY/AGRP neurons 15 which, in direct synaptic contact with anorectic POMC/CART neurons in the arcuate nucleus, 30 integrates gut hormone signals such as PYY . 31,32 Hence, Y2R mediates negative regulation of NPY signaling, and indirectly upregulation of POMC/CART, through PYY and NPY. 7 Peripheral administration of PYY in rodents reduces NPY mRNA levels and increases the POMC mRNA levels in the arcuate nucleus, as well as reduces food intake, but has no effect in fasted Y2R knockout mice.…”
Section: Discussionmentioning
confidence: 99%